2009
DOI: 10.1177/0890334408326071
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Psychological Factors on Breastfeeding Duration, Phase 1: Perceptions of Mothers and Clinicians

Abstract: Breastfeeding duration rates in Australia are low, prompting a search for modifiable factors capable of increasing the duration of breastfeeding. In this study, participants were asked which psychological factors they believed influence breastfeeding duration. Participants included 3 groups of mothers who had breastfed for varied lengths of time (n = 17), and 1 group of breastfeeding clinicians (n = 4). The nominal group technique was employed, involving a structured group meeting progressing through several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…The literature consistently shows that socio-demographic factors as maternal age, socio-economic status, level of education, marital status and place of residence are associated with both, breastfeeding initiation and maintenance [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature consistently shows that socio-demographic factors as maternal age, socio-economic status, level of education, marital status and place of residence are associated with both, breastfeeding initiation and maintenance [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies describe the influence of single predictive factors on breast feeding initiation and maintenance [7][8][9]. The literature consistently shows that socio-demographic factors as maternal age, socio-economic status, level of education, marital status and place of residence are associated with both, breastfeeding initiation and maintenance [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Another Australian study 23 used NGT to canvass insights from clinicians as part of a mixed methods investigation of nursing documentation. In a Queensland study, 24,25 NGT was used to explore what psychological factors may influence the duration of breastfeeding. Four groups were created; three constituted breastfeeding mothers and the final group consisted of lactation experts or midwives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have identified that BFSE is an important factor in breastfeeding outcomes including duration [12-14]. One study has identified that feeding method as planned is a predictor of BFSE [12].…”
Section: Introductionmentioning
confidence: 99%